Plant-based dietary patterns and ultra-processed food consumption - Chang, Kiara (2024)
Funding Information: National Institute for Health and Care Research (NIHR) School for Public Health Research, World Cancer Research Fund.This study is supported by the National Institute for Health and Care Research (NIHR) School for Public Health Research (SPHR) (Grant Reference Number NIHR 204000). The views expressed are those of the authors and not necessarily those of the NIHR or the Department of Health and Social Care. Funding for grant IIG_FULL_2020_033 was obtained from World Cancer Research Fund (WCRF UK), as part of the World Cancer Research Fund International grant programme. CM is supported by the NIHR Global Health Research Centre on NCDs and Environmental Change (NIHR203247). The funders had no role in study design, data collection, data analysis, interpretation of study findings, writing of the report, or decision to submit the paper for publication. Where authors are identified as personnel of the International Agency for Research on Cancer/World Health Organization, the authors alone are responsible for the views expressed in this article and they do not necessarily represent the decisions, policy or views of the International Agency for Research on Cancer/World Health Organization. This research has been conducted using the UK Biobank Resource under Application Number 29239. The authors would like to thank the participants of the UK Biobank study. Funding Information: This study is supported by the National Institute for Health and Care Research (NIHR) School for Public Health Research (SPHR) (Grant Reference Number NIHR 204000). The views expressed are those of the authors and not necessarily those of the NIHR or the Department of Health and Social Care. Funding for grant IIG_FULL_2020_033 was obtained from World Cancer Research Fund (WCRF UK), as part of the World Cancer Research Fund International grant programme. CM is supported by the NIHR Global Health Research Centre on NCDs and Environmental Change (NIHR203247). The funders had no role in study design, data collection, data analysis, interpretation of study findings, writing of the report, or decision to submit the paper for publication. Publisher Copyright: © 2024